Productive Waqf: The Power Of Sustainability - Ahmad Rizki Halomoan (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
This article discusses a new paradigm on waqf management in a way that is different from the classical approach applied by the muslim community decades ago. Nowadays, the demand for a more productive waqf management is increasing due to the society’s needs for a more sustainable financial security. This article is a the result of a literature review that focuses on the descriptive analysis of the diversification and management of waqf in Indonesia. The purpose of this article is to provide an explanation on how the waqf diversification and management in Indonesia can and should provide better financial security to the people who are qualified for waqf.